A Method for Analyzing the Dynamic Response of a Structural System with Variable Mass, Damping and Stiffness. (2001) - Zhang, Mike D.R.; Sun, Huanchun; Song, Yaxin
Abstract : In this paper, a method for analyzing the dynamic response of a structural system with variable mass, damping and stiffness is first presented. The dynamic equations of the structural system with variable mass and stiffness are derived according to the whole working process of a bridge bucket unloader. At the end of the paper, an engineering numerical example is given.